2016
DOI: 10.1016/j.aquaculture.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phosphorous and protein supplementation enhances seawater growth and reduces severity of vertebral malformation in triploid Atlantic salmon (Salmo salar L.)

Abstract: Diploid (2N) and triploid (3N) sibling post-smolts were divided between six sea pens and fed: a standard nutrient package diet (2 x 2N SP, 2 x 3N SP), or an iso-energetic nutrient boosted package (2 x 3N BP) until market size. 3N groups initially grew significantly faster than 2N, and by harvest, 3N BP weighed significantly more (3210 ± 87g) than 2N SP or 3N SP (3007± 64g; 2965 ± 88g), while there was no significant difference in weight between ploidy in SP diet. Higher visible vertebral (9.6 ± 0.4%) and jaw d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 57 publications
1
32
1
Order By: Relevance
“…; Smedley et al . ). Overall in Atlantic salmon, the development of lower jaw skeletal anomalies has been associated with several factors such as genetic predisposition especially in triploids (Sadler et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Smedley et al . ). Overall in Atlantic salmon, the development of lower jaw skeletal anomalies has been associated with several factors such as genetic predisposition especially in triploids (Sadler et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, LJD has been linked to a lack of dietary phosphorus (Roberts, Hardy & Sugiura 2001;Fjelldal et al 2016). The findings of Fjelldal et al (2016) suggest that LJD may occur anytime in early development when fish are not supplied with an appropriate amount of dietary P. Furthermore, it has been shown that triploids have a higher dietary P requirement than diploids (Fjelldal et al 2016;Smedley et al 2016). Overall in Atlantic salmon, the development of lower jaw skeletal anomalies has been associated with several factors such as genetic predisposition especially in triploids (Sadler et al 2001), a deficiency in dietary elements (Sadler et al 2001), high growth rates (King & Lee 1993;Taylor et al 2014;Fraser et al 2015), high incubation temperatures (Fraser et al 2015) and the different requirements for phosphorus in triploids (Fjelldal et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of deformed vertebrae in triploid salmon fed low P diet (1%, total P) was threefold higher compared with diploids (Smedley et al . ). Increasing the level of dietary phosphorus (1.2–1.4%, total P) effectively reduced the incidence of these anomalies in triploid salmon (Fjelldal et al .…”
Section: Phosphorus – the Pivotal Point Of Investigationmentioning
confidence: 97%
“…; Smedley et al . ). Correlation regression analysis of literature data revealed that the relation between dietary P and skeletal deformities is to a greater extent significant in triploids, than diploids, although the variation was high within triploids (Fig.…”
Section: Phosphorus – the Pivotal Point Of Investigationmentioning
confidence: 97%
See 1 more Smart Citation